Wireless Microcurrent Stimulation Therapy for Wound Healing - Dewi Lumanauw, Debryna; A. Pangayoman, Roys (Cermin Dunia Kedokteran, 2017)
Wound healing is a complex process to restore the normal function, structure and integrity of body cells after injury. All wounds will advance to three phases: inflammatory, proliferative and maturation. When the sequence of healing does not go in timely and orderly manner, the wound becomes chronic and more difficult to heal. Chronic, nonhealing wounds require a tailored management. The most fundamental pillars are adequate debridement, managing underlying diseases/factors and applying proper dressings. Additional novel adjuvant therapies, such as electrical stimulation, hyperbaric chamber and ultrasound, are currently being developed. Wireless microcurrent stimulation (WMCS) is a new method for wound healing. Studies have recommended the use of WMCS, considering the safety, easy to use, and benefits.Penyembuhan luka adalah proses kompleks untuk mengembalikan fungsi dan integritas seluler dan biokimiawi normal jaringan setelah terjadi luka. Semua luka akan melewati fase inflamasi, proliferasi dan maturasi hingga tercapai penyembuhan. Apabila proses penyembuhan tidak teratur dan tidak sesuai dengan waktu yang diharapkan, luka dapat menjadi kronis. Penanganan luka kronis memerlukan pendekatan yang sesuai dan dinamis. Pilar terpenting adalah debridement adekuat, mengatasi faktor-faktor predisposisi lain dan pemilihan dressing yang tepat. Terapi tambahan lain seperti electrical stimulation (ES), hyperbaric chamber dan ultrasound. Wireless microcurrent stimulation (WMCS) merupakan perkembangan terbaru terapi ES. Beberapa penelitian membuktikan bahwa manfaat WMCS sama dengan metode konvensional, bahkan dapat menjadi pilihan terbaik karena aman, tidak mengiritasi, mudah dipindahkan dan digunakan.